2021
DOI: 10.1109/tgcn.2021.3067918
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Learning-Enabled Green Communication for Next-Generation Wireless Systems

Abstract: Next generation wireless systems have witnessed significant R&D attention from academia and industries to enable wide range of applications for connected environment around us. The technical design of next generation wireless systems in terms of relay and transmit power control is very critical due to the ever-reducing size of these sensor enabled systems. The growing demand of computation capability in these systems for smart decision making further diversified the significance of relay and transmit power con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 30 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…In [18], the authors compared the performance of PSO and differential evolution (DE) algorithms for resource allocation in ad hoc networks of quantum-enabled IoT devices. The simulation results showed that the DE algorithm outperformed the PSO algorithm in terms of energy consumption and data transmission rate.…”
Section: Comparison Of Previous Optimization Algorithmsmentioning
confidence: 99%
“…In [18], the authors compared the performance of PSO and differential evolution (DE) algorithms for resource allocation in ad hoc networks of quantum-enabled IoT devices. The simulation results showed that the DE algorithm outperformed the PSO algorithm in terms of energy consumption and data transmission rate.…”
Section: Comparison Of Previous Optimization Algorithmsmentioning
confidence: 99%
“…It includes a group of search agents that explore the most feasible output depending on randomization and few specific rules. These rules are nature-inspired [26,27]. Lee and Teng proposed an improved version for LEACH clustering protocol to reduce packet loss rate as well as to prolong the network lifetime using fuzzy inference systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 5 , 6 However, it is difficult for most classical cryptographic algorithms to ensure long-term security of the data stored in the remote cloud due to upcoming quantum computers and fast quantum algorithms. 7 , 8 , 9 Especially, quantum supremacy (or quantum advantage) has been demonstrated, 10 , 11 so classical cryptography will certainly face lots of threats and challenges.…”
Section: Introductionmentioning
confidence: 99%